Biomechanical Analysis of Decellularized Human Umbilical Veins Following Sodium Dodecyl Sulphate Treatment - Sulistyaningsih, Ni Kadek; Limanto, Danang Himawan; Sembiring, Yan Efrata (Journal of Neonatal Surgery, 2025)
Background: The decellularization procedure aims to make tissue engineering-vessel grafts (TEVG) made of biologic material, such as xenograft and allograft materials, less immunogenic to prevent graft rejection. Human umbilical veins are known as a potential scaffold material for making TEVG because they already have a basic blood vessel structure and are easy to obtain. Sodium dodecyl sulphate (SDS) is an effective decellularization agent and can maintain the extracellular matrix well. Objective: This study aim to assess whether the biomechanical properties are maintained after decellularization using SDS to determine whether the graft is predicted to be functional. Materials and Methods: This is an in-vitro experimental study involving the decellularization process of umbilical vein scaffolds using SDS at concentrations of 0.5% and 1% with a duration of 12 hours and 24 hours. The biomechanical features tested were tensile strength, Young's modulus, burst pressure, and suture holding capacity. Results: The biomechanical results after decellularization with SDS proved quite effective in preserving the umbilical vein's biomechanics. Immersion in 0.5% SDS for 24 hours showed the biomechanical results closest to the control. Conclusions: A low-concentration SDS agent with 24-hour immersion is effective in removing cellular material, as seen from histology results, and it is still able to maintain the biomechanics of the human umbilical vein scaffold.